2012
DOI: 10.1143/jjap.51.05ec03
|View full text |Cite
|
Sign up to set email alerts
|

Integration Process Development for Improved Compatibility with Organic Non-Porous Ultralow-k Dielectric Fluorocarbon on Advanced Cu Interconnects

Abstract: A method suggested by Holevo is used to obtain a lower bound for the information capacity of a quantum narrow-band free-space link without extraneous noise. At high photon rates the bound is better than those previously proposed and comes close to a fundamental upper bound. It is not so good at low rates, where it is beaten by photon-detecting systems. The normal modes are not treated as independent channels. A system is describeo where the normal modes are used in pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…The nonporous structure is considered the reason for the lack of an increase in the leakage current, preventing moisture absorption in the bulk fluorocarbon film from chemicals, which is in a good agreement with our previous result that no increase of leakage current of fluorocarbon was found after cleaning by diluted hydrogen fluoride (DHF). 12,28 Moreover, further degradation of the leakage current was observed as the over-polishing ratio increased in Fig. 4 and this is consistent with the result in the damascene sample.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The nonporous structure is considered the reason for the lack of an increase in the leakage current, preventing moisture absorption in the bulk fluorocarbon film from chemicals, which is in a good agreement with our previous result that no increase of leakage current of fluorocarbon was found after cleaning by diluted hydrogen fluoride (DHF). 12,28 Moreover, further degradation of the leakage current was observed as the over-polishing ratio increased in Fig. 4 and this is consistent with the result in the damascene sample.…”
Section: Resultssupporting
confidence: 87%
“…[1][2][3][4][5][6] An organic non-porous ULK dielectric, fluorocarbon (k = 2.2), has been integrated into Cu damascene interconnects as an alternative dielectric to avoid integration-process-induced damage in LSI fabrication. [7][8][9][10][11][12] The ULK dielectric fluorocarbon film was deposited using an advanced microwave (2.45 GHz) exited dual-showerplate structure plasma reactor. The microwave plasma produced by the radial line slot antenna indicates high density and low electron temperature (around 1-2 eV), which prevents ion bombardment damage to the substrates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] A fluorocarbon dielectric prepared by microwaveexcited-plasma-enhanced chemical vapor deposition (MWPE-CVD) has also been demonstrated and the film obtained has indicated a dielectric constant as low as 2.2 and contained no pores. [16][17][18] The authors have carried out tribological studies of brush scrubbing of fluorocarbon dielectric surfaces in PCC in order to obtain good electrical properties. 19,20) In these studies, the high rotation of the brush leading to increased fluid flow was suggested as the optimum condition to accomplish a satisfactory particle removal efficiency without scratch formation degradation and the electrical properties.…”
Section: Introductionmentioning
confidence: 99%